DUODENAL DİVERTİKÜLOSİS OLGULARINDA KLİNİK ANALİZ VE LİTERATÜRÜN GÖZDEN GEÇİRİLMESİ - ERSAN, Yılmaz; YAVUZ, Nihat; ÇİÇEK, Yusuf; ERGÜNEY, Sabri; KUŞASLAN, Ramazan; BELLİ, Ahmet (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Duodenal diverticular disease is an uncommon clinical entity; however, with progressive aging of the population, duodenal diverticulosis is encountered more often. Duodenal diverticula, discovered incidentally in patients during upper gastrointestinal examinations, are usually asymptomatic, but can be the source of significant morbidity. When duodenal divertucula are located near the major duodenal papilla, they are called juxtapapillary (periampullary) duodenal diverticula. The aim of this study was to investigate the requency, clinical characteristics, findings and possible varieties of treatment of duodenal diverticula in patients with duodenal diverticula. We retrospectively reviewed the cases of duodenal diverticulum undergone surgical treatment between 1983 and 2003. Clinical findings and pathological results were learned from records of cases. Results.- 25 patients with duodenal diverticula were treated at our clinic from 1983 to 2003. Their age was comprised between 43 and 80 years. Mean age of them was 58.1 years. Fifteen of cases were women (60%) while ten were men (40%). The second part of duodenum was involved in 15 cases (60%). The third part of duodenum was involved in 6 cases (24%) and the fourth in 4 cases (16%) Multiple diverticula were found only 2 cases. 9 patients had bilio-pancreatic symptoms including in recurrent episodes of cholangitis, progressive jaundice and abdominal pain. In patients with diverticula of third and fourth part, abdominal pain and vomiting were the main symptoms. Conclusions.- Diverticulectomy is an effective surgical procedure. Juxtapapillary duodenal diverticula are important causative factors in the formation of biliary stones.